Open Design Systems - A.R.M. Wolfert (TU Delft OPEN Publishing, 2023)
Current systems design and decision management methodologies can be single-sided, ignoring or failing to capture the dynamic interplay between multi-stakeholder preferences ('what they want') and system performances ('what they can'). In addition, these methodologies often contain fundamental modelling errors and do not provide single best-fit solutions. This leaves designers or decision-makers without unique answers to their problems. Above all, mainstream higher education primarily applies instructivist and research-based learning methods, and therefore does not adequately prepare students for designing solutions to future complex problems. This book introduces both a state-of-the-art participatory design methodology (Odesys), and a design-based learning concept (ODL), which together overcome the aforementioned issues. Odesys is a pure act of open design integration to confront conflicting socio-technical interests and is the key to unlocking these complexities to deliver socially responsible systems. Odesys' design engine, the Preferendus, enables stakeholders to cooperatively identify their best-fit design synthesis. It employs a novel optimisation method that maximises the aggregated preferences, integrating sound mathematical and extended U-modelling via open technical-, social-, and purpose cycles. The art of ODL is a constructivist design-based and well-proven learning concept fostering students' design capabilities to become open and persistent problem solvers. It is a reflective, creative, and engaged learning approach that opens human development and unlocks new knowledge and solutions. The author also introduces new management features such as the corporate social identifier (CSI), the 'socio-eco' threefold organization model and U-model based open loop management. Finally, the author places Odesys & ODL within the integrative context of empiricism, rationalism, spiritualism, and constructivism to unite the open design impulse. This book will be of interest to both academics and practitioners working in the field of complex systems design and managerial decision-making, and functions as a textbook on systems design and management for master students from diverse backgrounds. DOI: 10.3233/RIDS10
Keywords: 650; Management; Technology; Engineering